Dose–response relationship between obstructive sleep apnoea severity and C-reactive protein levels: data from the European Sleep Apnoea Database - Grote, Ludger; Gouveris, Haralampos; Lethuillier, Lea; Verbraecken, Johan; Basoglu, Ozen K.; Schiza, Sophia; Ludka, Ondrej; Ryan, Silke; Joppa, Pavol; Fanfulla, Francesco; Mihaicuta, Stefan; Saaresranta, Tarja; et al. (European Respiratory Society (ERS), 2026)
Introduction
Obstructive sleep apnoea (OSA) characterised by intermittent hypoxia promotes systemic inflammation. This study evaluated the association between OSA severity and circulating C-reactive protein (CRP) levels as marker of systemic inflammation in a pan-European patient cohort.
Methods
This cross-sectional analysis of the multicentre European Sleep Apnoea Database (ESADA) cohort used inverse probability weighted regression adjustment for multiple covariates within a linear mixed-effects model (LMEM) to test the independent association between OSA severity and CRP levels. Covariates included anthropometrics and comorbidities. Study centre and year of analysis accounted for methodological variability in CRP analysis.
Results
18 445 subjects (71% male, median age 53 years (interquartile range 44–62), median apnoea–hypopnoea index (AHI) 22.1 events per h (9–44.9)) were included. CRP (median 3.0 mg·L−1 (1.2–5.1)) increased in a dose–response fashion across OSA severity categories (2.0 (1.0–4.0) for AHI <5 events per h; 2.5 (1.0–5.0) for AHI 5–<15 events per h); 2.9 (1.2–5.0) for AHI 15–<30 events per h; and 3.7 mg·L−1 (1.8–6.4) for AHI ≥30 events per h; p<0.001, respectively). In the final LMEM model, AHI remained an independent predictor of CRP concentration (p<0.001). Other significant predictors of CRP were age and female sex. Obesity (body mass index ≥35 kg·m−2) had, among other comorbidities, the strongest independent effect on CRP levels with 2.7 mg·L−1 (95% CI 2.45–2.90).
Conclusions
Our results showed a consistent and robust dose–response relationship between OSA severity and systemic inflammation independent of usual confounders. The combination of OSA and obesity amplified the association. Future studies should address whether elevated CRP could serve as a prognostic marker for subsequent cardiovascular events in OSA.